Electrolyte for zinc-manganese battery

By modifying the grafted pyridine groups on the surface of zinc oxide, forming coordination bonds to enhance the corrosion inhibition effect, the problem of self-corrosion of zinc-manganese batteries is solved, the battery life and performance is improved, and the battery stability and safety is achieved. .

CN119133492AActive Publication Date: 2024-12-13JIAXING HENGWEI BATTERY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411284319.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

There is self-corrosion during storage of alkaline zinc-manganese batteries, resulting in a shortening of battery life. The existing corrosion inhibitors may affect the battery's vibration resistance and leakage resistance while improving the battery's performance.

Method used

By modifying the surface of zinc oxide, grafting the pyridine groups, forming nitrogen atoms and π electron coordination bonds with lonely pairs of electrons, enhancing the corrosion inhibition effect, forming a protective layer to inhibit self-corrosion of the zinc electrode, and modifying it Zinc oxide is used in the electrolyte of zinc-manganese batteries.

Benefits of technology

It significantly improves the storage life and battery performance of zinc-manganese batteries, reduces side reactions, enhances the stability of the electrode/electrolyte interface, reduces the gas discharge volume, and improves the safety and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005042675410000091
    Figure BDA0005042675410000091
  • Figure BDA0005042675410000101
    Figure BDA0005042675410000101
  • Figure BDA0005042675410000111
    Figure BDA0005042675410000111
Patent Text Reader

Abstract

The invention relates to the technical field of methods or devices for directly converting chemical energy into electric energy, in particular to an electrolyte for a zinc-manganese battery. The electrolyte comprises potassium hydroxide, modified zinc oxide and water. The invention also provides a preparation method of the composition. Compared with the prior art, the electrolyte provided by the invention has excellent corrosion inhibition effect and good conductivity, and can prolong the service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of methods or devices for directly converting chemical energy into electrical energy, and in particular to an electrolyte for zinc-manganese batteries. Background Art

[0002] Compared with rechargeable batteries (secondary batteries) such as nickel-cadmium, nickel-metal hydride and lithium, disposable zinc-manganese batteries have the following advantages: First, in terms of safety, disposable batteries have higher guarantees. They are not prone to safety issues such as leakage or explosion, and can be used safely without relying on protective circuit boards. Second, they show better stability, are not affected by memory effects, and there is no need to worry about over-discharge. They are more adaptable to the use environment and are less likely to be damaged. Third, there is no need to carry a charger when using disposable batteries. Their discharge cycle is usually longer than that of rechargeable batteries, and they are plug-and-play, providing greater convenience for users. In addition, compared with rechargeable batteries, disposable batteries are lower in cost and more cost-effective for small or low-power electronic devices. Finally, most of the current disposable zinc-manganese batteries have been mercury-free or low-mercury, with less impact on the environment and easy to recycle and dispose of.

[0003] Alkaline zinc-manganese batteries are characterized by low internal resistance, strong voltage recovery ability after discharge, and a wide operating temperature range between -20°C and 60°C, which makes them suitable for use in high-cold areas. Their large current continuous discharge capacity is about 5 times that of acid zinc-manganese batteries. In addition, their low-temperature discharge performance is also very good, and they do not contain mercury and cadmium, making them environmentally friendly. Alkaline zinc-manganese batteries are widely used in various life scenarios, such as electric toys, household appliances, smart homes, home medical equipment, outdoor electronic equipment, etc. With the advancement of technology, the performance of alkaline zinc-manganese batteries has been significantly improved, including higher energy density, wider operating temperature range, and less self-discharge rate.

[0004] CN108172854A discloses a zinc-manganese battery, specifically an alkaline zinc-manganese battery containing zinc oxide and a preparation method thereof, wherein the battery comprises a negative electrode zinc paste made of zinc powder, zinc oxide, sodium silicate and a binder, a positive electrode ring made of electrolytic manganese dioxide and a conductive agent, and a diaphragm made of pulp or fiber mixture, and electrolytes for the positive electrode ring, the negative electrode zinc paste and the diaphragm, respectively, wherein the electrolytes are all potassium hydroxide aqueous solutions, wherein the electrolyte used for the negative electrode zinc paste contains zinc oxide. The invention proposes that based on the premise of the growing market demand for high-power alkaline zinc-manganese batteries, the utilization rate of zinc powder is increased while the hydrogen evolution of zinc powder is suppressed to a certain extent, and the high current discharge performance of the alkaline zinc-manganese battery produced by the formula is significantly improved with the optimized positive and negative electrodes of the battery and the concentration ratio of the alkali solution.

[0005] CN107275655A discloses a natural extract composition for zinc-manganese battery electrolyte and its use, zinc-manganese battery electrolyte and zinc-manganese battery, the composition includes imidazoline derivatives, amino acid derivatives and sterol derivatives; the composition of the invention has excellent corrosion inhibition effect and good electrical conductivity, low temperature resistance and high temperature resistance; when used as an electrolyte of zinc-manganese battery, it can inhibit the self-discharge performance of negative electrode materials in non-working state, thereby reducing the self-consumption of the battery and greatly extending the service life of the battery, and in battery operation, due to good electrical conductivity, it can exert normal battery performance; more importantly, the composition does not contain heavy metal mercury, avoiding heavy metal pollution that may be caused by discarded batteries, reducing subsequent processing costs and environmental pollution risks. Its low temperature resistance can reach -30°C and high temperature resistance can reach 100°C.

[0006] The electrodes of alkaline zinc-manganese batteries have a certain self-corrosion phenomenon, which causes a certain reduction in the storage life of zinc-manganese batteries. Therefore, to solve the problem of improving the storage life of alkaline zinc-manganese batteries, we can start from the essence of battery self-corrosion. In alkaline zinc-manganese batteries, since metal zinc is in a thermodynamically unstable state in an alkaline environment, metal zinc is prone to chemical reactions in this state to produce hydrogen, resulting in self-corrosion. This is because zinc, as an active metal, reacts with potassium hydroxide (KOH) in an alkaline electrolyte, causing zinc to dissolve and then form zinc corrosion products, such as zinc hydroxide (Zn(OH) 2 ) and zinc oxide (ZnO). In addition, during the discharge process of the battery, the zinc at the negative electrode loses electrons, undergoes an oxidation reaction, and produces zinc ions. These zinc ions combine with hydroxide ions to form zinc hydroxide, which is also one of the reasons for the occurrence of self-corrosion. In order to slow down this self-corrosion phenomenon, researchers have taken a variety of measures. For example, using corrosion-resistant zinc alloys as negative electrodes or adding zinc corrosion inhibitors, such as inorganic corrosion inhibitors such as metal oxides, hydroxides, and inorganic salts, as well as organic corrosion inhibitors such as surfactants and dehydrogenation additives. These corrosion inhibitors can form a protective film on the zinc surface to prevent or reduce OH - Ions come into contact with the zinc surface, thereby inhibiting the corrosion of the electrode. However, it should be noted that non-mercury corrosion inhibitors may have some disadvantages, such as increasing the internal resistance of the battery, affecting the contact between zinc powder particles and between zinc powder and the current collector, reducing the vibration resistance of the battery, and the leakage resistance during discharge is inferior to that of mercury-containing batteries. In the process of manufacturing mercury-free batteries, the first thing to solve is the problem of battery anode corrosion, which is also the key to solving the problem of battery storage life at the current stage. Summary of the invention

[0007] In view of the above-mentioned defects in the prior art, the technical problem to be solved by the present invention is to provide an electrolyte for zinc-manganese battery and a preparation method thereof.

[0008] The negative electrode electrolyte of alkaline zinc-manganese battery is mainly composed of KOH and ZnO. KOH provides conductive ions when the battery is discharged, and its concentration affects the charge transfer capacity of the battery during discharge. ZnO mainly inhibits the self-dissolution of zinc in the negative electrode, that is, the self-corrosion of zinc. The role of ZnO in alkaline zinc-manganese batteries is mainly to inhibit the self-dissolution of zinc in the negative electrode by forming a protective film. As an amphoteric substance, ZnO can form a dissolution equilibrium with zincate in potassium hydroxide (KOH) solution. When the battery is discharged, zincate is produced at the negative electrode, and ZnO will be deposited when its concentration reaches saturation. This ZnO protective film can slow down the further reaction of zinc, thereby protecting the zinc electrode from excessive dissolution or corrosion. In addition, the addition of ZnO can also help improve the electrochemical performance of the battery. In some studies, by in-situ growing a ZnO protective layer on the surface of zinc metal, the cycle stability of the zinc negative electrode can be significantly improved and dendrite growth can be inhibited, thereby extending the service life of the battery. The presence of the ZnO protective layer helps to form a stable electrode / electrolyte interface, reduce the occurrence of side reactions, and thus improve the overall performance of the battery. The present invention provides a modified ZnO, wherein a pyridine group is grafted onto the surface of the modified ZnO. The pyridine group contains nitrogen atoms with lone pairs of electrons, and these lone pairs of electrons can form coordination bonds with atoms on the metal surface to achieve chemical adsorption. In addition, the π electrons on the pyridine ring can form coordination bonds with empty orbitals on the metal surface to enhance the corrosion inhibition effect. Therefore, after the modified zinc oxide forms a protective layer on the surface of the zinc negative electrode, the corrosion inhibition effect is enhanced. Applying the modified zinc oxide to the electrolyte for zinc-manganese batteries can further improve the battery life.

[0009] To achieve the above object, the present invention provides an electrolyte for a zinc-manganese battery, comprising potassium hydroxide, modified zinc oxide and water;

[0010] The preparation method of the modified zinc oxide comprises the following steps:

[0011] After the zinc oxide is dried in vacuo, anhydrous ethanol and water are mixed in proportion, the dried zinc oxide is added to the mixture of ethanol and water, and ultrasonically dispersed at 400-500W for 30-50min, stirred for 1-2h after the ultrasonication, and then an equal volume of trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane ethanol solution is added dropwise, and the temperature is raised and stirred for 1-3h after the addition is completed, and then cooled to room temperature. The mixed solution is washed 3 times with anhydrous ethanol, centrifuged, the supernatant is discarded, and the lower precipitate is vacuum dried to obtain modified zinc oxide.

[0012] Furthermore, the mass ratio of the anhydrous ethanol to water is 1:1-2.

[0013] Furthermore, the mass ratio of the zinc oxide to the mixed solution of ethanol and water is 1:80-100.

[0014] Furthermore, the temperature range of the heating is 60-80°C.

[0015] Furthermore, the concentration of the trimethoxy-[4-[2-(4-methyl-2-pyridyl)-4-pyridyl]butyl]silane ethanol solution is 4 to 5 wt%.

[0016] Furthermore, the vacuum drying temperature is 50-60°C.

[0017] Furthermore, the vacuum drying time is 8 to 10 hours.

[0018] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0019] Mix potassium hydroxide, modified zinc oxide and water, and stir evenly to obtain the product.

[0020] Furthermore, the concentration of potassium hydroxide is 25-40wt%.

[0021] Furthermore, the concentration of the modified zinc oxide is 2-8 wt %.

[0022] Beneficial effects of the present invention:

[0023] Compared with the prior art, the present invention provides a modified ZnO, by modifying its surface and grafting pyridine groups, the pyridine groups contain nitrogen atoms with lone pairs of electrons, these lone pairs of electrons can form coordination bonds with atoms on the metal surface to achieve chemical adsorption. In addition, the π electrons on the pyridine ring can form coordination bonds with empty orbitals on the metal surface to enhance the corrosion inhibition effect. Therefore, after the modified zinc oxide forms a protective layer on the surface of the zinc negative electrode, the corrosion inhibition effect is enhanced, and the application of the modified zinc oxide to the electrolyte for zinc-manganese batteries can further improve the battery life. DETAILED DESCRIPTION

[0024] Trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane, CAS No.: 1588918-82-4.

[0025] 2-(2-pyridinyl)ethyltrimethoxysilane, trimethoxy(2-pyridin-2-ylethyl)silane, CAS number: 27326-65-4.

[0026] Zinc oxide, particle size: 20-30nm.

[0027] Example 1

[0028] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0029] Mix 40 g of potassium hydroxide, 6 g of modified zinc oxide and 54 mL of water, and stir evenly to obtain the product.

[0030] The preparation method of the modified zinc oxide comprises the following steps:

[0031] After the zinc oxide was dried at 60°C in vacuum for 8 hours, anhydrous ethanol and water were mixed in a mass ratio of 1:1.6, 6 g of the dried zinc oxide was added to a mixture of 600 g of ethanol and water, and ultrasonically dispersed at 450W for 40 minutes. After the ultrasonication, the mixture was stirred for 1 hour, and then an equal volume of 4 wt% trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane ethanol solution was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for 2 hours. After cooling to room temperature, the mixture was washed 3 times with anhydrous ethanol, centrifuged, the supernatant was discarded, and the lower precipitate was vacuum dried at 60°C for 10 hours to obtain modified zinc oxide.

[0032] Example 2

[0033] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0034] Mix 25 g of potassium hydroxide, 6 g of modified zinc oxide and 69 mL of water, and stir evenly to obtain the product.

[0035] The preparation method of the modified zinc oxide comprises the following steps:

[0036] After the zinc oxide was dried at 60°C in vacuum for 8 hours, anhydrous ethanol and water were mixed in a mass ratio of 1:1.6, 6 g of the dried zinc oxide was added to a mixture of 600 g of ethanol and water, and ultrasonically dispersed at 450W for 40 minutes. After the ultrasonication, the mixture was stirred for 1 hour, and then an equal volume of 4 wt% trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane ethanol solution was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for 2 hours. After cooling to room temperature, the mixture was washed 3 times with anhydrous ethanol, centrifuged, the supernatant was discarded, and the lower precipitate was vacuum dried at 60°C for 10 hours to obtain modified zinc oxide.

[0037] Example 3

[0038] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0039] Mix 30 g of potassium hydroxide, 6 g of modified zinc oxide and 64 mL of water, and stir evenly to obtain the product.

[0040] The preparation method of the modified zinc oxide comprises the following steps:

[0041] After the zinc oxide was dried at 60°C in vacuum for 8 hours, anhydrous ethanol and water were mixed in a mass ratio of 1:1.6, 6 g of the dried zinc oxide was added to a mixture of 600 g of ethanol and water, and ultrasonically dispersed at 450W for 40 minutes. After the ultrasonication, the mixture was stirred for 1 hour, and then an equal volume of 4 wt% trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane ethanol solution was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for 2 hours. After cooling to room temperature, the mixture was washed 3 times with anhydrous ethanol, centrifuged, the supernatant was discarded, and the lower precipitate was vacuum dried at 60°C for 10 hours to obtain modified zinc oxide.

[0042] Example 4

[0043] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0044] Mix 35 g of potassium hydroxide, 6 g of modified zinc oxide and 59 mL of water, and stir evenly to obtain a product.

[0045] The preparation method of the modified zinc oxide comprises the following steps:

[0046] After the zinc oxide was dried at 60°C in vacuum for 8 hours, anhydrous ethanol and water were mixed in a mass ratio of 1:1.6, 6 g of the dried zinc oxide was added to a mixture of 600 g of ethanol and water, and ultrasonically dispersed at 450W for 40 minutes. After the ultrasonication, the mixture was stirred for 1 hour, and then an equal volume of 4 wt% trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane ethanol solution was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for 2 hours. After cooling to room temperature, the mixture was washed 3 times with anhydrous ethanol, centrifuged, the supernatant was discarded, and the lower precipitate was vacuum dried at 60°C for 10 hours to obtain modified zinc oxide.

[0047] Example 5

[0048] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0049] Mix 45 g of potassium hydroxide, 6 g of modified zinc oxide and 49 mL of water, and stir evenly to obtain the product.

[0050] The preparation method of the modified zinc oxide comprises the following steps:

[0051] After the zinc oxide was dried at 60°C in vacuum for 8 hours, anhydrous ethanol and water were mixed in a mass ratio of 1:1.6, 6 g of the dried zinc oxide was added to a mixture of 600 g of ethanol and water, and ultrasonically dispersed at 450W for 40 minutes. After the ultrasonication, the mixture was stirred for 1 hour, and then an equal volume of 4 wt% trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane ethanol solution was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for 2 hours. After cooling to room temperature, the mixture was washed 3 times with anhydrous ethanol, centrifuged, the supernatant was discarded, and the lower precipitate was vacuum dried at 60°C for 10 hours to obtain modified zinc oxide.

[0052] Example 6

[0053] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0054] Mix 40 g of potassium hydroxide, 2 g of modified zinc oxide and 58 mL of water, and stir evenly to obtain the product.

[0055] The preparation method of the modified zinc oxide comprises the following steps:

[0056] After the zinc oxide was dried at 60°C in vacuum for 8 hours, anhydrous ethanol and water were mixed in a mass ratio of 1:1.6, 6 g of the dried zinc oxide was added to a mixture of 600 g of ethanol and water, and ultrasonically dispersed at 450W for 40 minutes. After the ultrasonication, the mixture was stirred for 1 hour, and then an equal volume of 4 wt% trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane ethanol solution was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for 2 hours. After cooling to room temperature, the mixture was washed 3 times with anhydrous ethanol, centrifuged, the supernatant was discarded, and the lower precipitate was vacuum dried at 60°C for 10 hours to obtain modified zinc oxide.

[0057] Example 7

[0058] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0059] Mix 40 g of potassium hydroxide, 4 g of modified zinc oxide and 56 mL of water, and stir evenly to obtain the product.

[0060] The preparation method of the modified zinc oxide comprises the following steps:

[0061] After the zinc oxide was dried at 60°C in vacuum for 8 hours, anhydrous ethanol and water were mixed in a mass ratio of 1:1.6, 6 g of the dried zinc oxide was added to a mixture of 600 g of ethanol and water, and ultrasonically dispersed at 450W for 40 minutes. After the ultrasonication, the mixture was stirred for 1 hour, and then an equal volume of 4 wt% trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane ethanol solution was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for 2 hours. After cooling to room temperature, the mixture was washed 3 times with anhydrous ethanol, centrifuged, the supernatant was discarded, and the lower precipitate was vacuum dried at 60°C for 10 hours to obtain modified zinc oxide.

[0062] Example 8

[0063] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0064] Mix 45 g of potassium hydroxide, 8 g of modified zinc oxide and 46 mL of water, and stir evenly to obtain the product.

[0065] The preparation method of the modified zinc oxide comprises the following steps:

[0066] After the zinc oxide was dried at 60°C in vacuum for 8 hours, anhydrous ethanol and water were mixed in a mass ratio of 1:1.6, 6 g of the dried zinc oxide was added to a mixture of 600 g of ethanol and water, and ultrasonically dispersed at 450W for 40 minutes. After the ultrasonication, the mixture was stirred for 1 hour, and then an equal volume of 4 wt% trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane ethanol solution was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for 2 hours. After cooling to room temperature, the mixture was washed 3 times with anhydrous ethanol, centrifuged, the supernatant was discarded, and the lower precipitate was vacuum dried at 60°C for 10 hours to obtain modified zinc oxide.

[0067] Comparative Example 1

[0068] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0069] Mix 40 g of potassium hydroxide, 6 g of zinc oxide and 54 mL of water, and stir evenly to obtain the product.

[0070] Comparative Example 2

[0071] A method for preparing an electrolyte for a zinc-manganese battery comprises the following steps:

[0072] Mix 45 g of potassium hydroxide, 8 g of modified zinc oxide and 46 mL of water, and stir evenly to obtain the product.

[0073] The preparation method of the modified zinc oxide comprises the following steps:

[0074] After the zinc oxide was dried at 60°C in vacuum for 8 hours, anhydrous ethanol and water were mixed in a mass ratio of 1:1.6, 6 g of the dried zinc oxide was added to a mixture of 600 g of ethanol and water, and ultrasonically dispersed at 450W for 40 minutes. After the ultrasonication, the mixture was stirred for 1 hour, and then an equal volume of 4 wt% 2-(2-pyridyl)ethyltrimethoxysilane ethanol solution was added dropwise. After the addition was completed, the mixture was heated to 70°C and stirred for 2 hours, cooled to room temperature, and the mixture was washed 3 times with anhydrous ethanol, centrifuged, the supernatant was discarded, and the lower precipitate was vacuum dried at 60°C for 10 hours to obtain modified zinc oxide.

[0075] Test Example 1

[0076] 60wt% nano zinc powder, 3wt% sodium silicate, and 2wt% sodium acrylate were dry mixed, and after being mixed, vacuum wet mixed was performed. During the mixing process, 35wt% electrolyte was added to obtain negative zinc paste. The positive electrode ring of the battery was assembled and injected with electrolyte. The electrolyte was injected into the diaphragm, and the diaphragm was allowed to stand until it was completely wetted. The negative zinc paste was injected into the battery, and alkaline zinc-manganese batteries containing the electrolytes described in each embodiment and control example were assembled. The prepared alkaline zinc-manganese batteries were tested for performance, and the specific results are shown in Table 1.

[0077] Table 1 Discharge performance test results of batteries containing electrolyte for zinc-manganese batteries

[0078]

[0079]

[0080] The discharge performance test of alkaline zinc-manganese batteries is an important indicator for evaluating the ability of batteries to provide electrical energy under actual conditions of use. The discharge capacity is the capacity of the battery, which indicates the amount of electricity discharged by the battery under certain conditions (standard discharge rate, temperature, termination voltage, etc.). Alkaline zinc-manganese batteries are widely used for their high energy density, high power density, good low temperature performance and long storage life. They usually use potassium hydroxide as the electrolyte, and electrolytic manganese dioxide as the positive electrode active material and zinc powder as the negative electrode active material. The discharge performance of alkaline zinc-manganese batteries is reflected in their low internal resistance, the ability to maintain a high stable voltage under heavy load, and high MnO 2Utilization rate. It can be seen from Table 1 that the alkaline zinc-manganese battery obtained by the present invention has long discharge time and many discharge times, and has excellent performance of large current discharge and long-term storage of the battery. From the test results, it can be seen that the concentration of potassium hydroxide and zinc oxide in the electrolyte will have a certain effect on the discharge performance. Compared with Examples 1 to 5, increasing the KOH concentration is beneficial to the continuous discharge performance of the battery. Compared with Examples 6 to 8, increasing the ZnO content in Example 1 is beneficial to the electrical performance of the battery. However, after increasing to a certain extent, the performance will not continue to improve with the increase in concentration. This is because as the concentration increases, the interaction between positive and negative ions increases, and the ion movement rate decreases, which reduces the conductivity.

[0081] Test Example 2

[0082] The alkaline zinc-manganese battery prepared in Test Example 1 was subjected to expansion and gas evolution performance tests, and the performance results are shown in Table 2, wherein the amount of gas evolution was measured by a gas collecting device. After the battery was subjected to a discharge test, it was disassembled and the amount of gas evolved per gram of the battery was tested using a gas collecting device. The leakage test is to place a certain number of samples of the experimental group in a 60°C high temperature box, keep it at a constant temperature for 168 hours, and observe whether the battery leaks. The safety test indicates whether the battery can maintain normal operation under the safety hazards caused by short circuit, over discharge, and forced current (i.e. forced current cathodic protection).

[0083] Table 2 Performance test results of batteries containing electrolyte for zinc-manganese batteries

[0084]

[0085] From the test in Table 2, it can be seen that the battery prepared by the electrolyte of the present invention has good safety performance. Compared with Examples 1 to 5, too low KOH concentration will increase the amount of gas evolution after partial discharge of the battery. Compared with Examples 6 to 8, too low ZnO content in Example 1 will also increase the amount of gas evolution of the battery. Therefore, there is an optimal addition amount for both KOH and ZnO. Compared with Control Example 1, Example 1 modifies zinc oxide by modifying its surface and grafting pyridine groups. The pyridine groups contain nitrogen atoms with lone pairs of electrons. These lone pairs of electrons can form coordination bonds with atoms on the metal surface to achieve chemical adsorption. In addition, the π electrons on the pyridine ring can form coordination bonds with empty orbitals on the metal surface to enhance the corrosion inhibition effect. The improvement of the corrosion inhibition effect means a reduction in the activity of the zinc electrode, thereby effectively inhibiting the self-corrosion of the zinc electrode and reducing the amount of gas evolution. Therefore, the modified zinc oxide can further improve the battery life. Compared with Control Example 2, in Example 1, the trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane used for grafting modification has more pyridine groups, so the corrosion inhibition effect is better than that of Control Example 2, and thus the amount of gas evolution is less.

[0086] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. An electrolyte for a zinc-manganese battery, characterized in that: comprising potassium hydroxide, modified zinc oxide and water; The preparation method of the modified zinc oxide comprises the following steps: After the zinc oxide is dried in vacuo, anhydrous ethanol and water are mixed in proportion, the dried zinc oxide is added to the mixture of ethanol and water, and ultrasonically dispersed at 400-500W for 30-50min, stirred for 1-2h after the ultrasonication, and then an equal volume of trimethoxy-[4-[2-(4-methyl-2-pyridinyl)-4-pyridinyl]butyl]silane ethanol solution is added dropwise, and the temperature is raised and stirred for 1-3h after the addition is completed, and then cooled to room temperature. The mixed solution is washed 3 times with anhydrous ethanol, centrifuged, the supernatant is discarded, and the lower precipitate is vacuum dried to obtain modified zinc oxide.

2. The electrolyte for zinc-manganese battery according to claim 1, characterized in that: The mass ratio of the anhydrous ethanol to water is 1:1-2.

3. The electrolyte for zinc-manganese battery according to claim 1, characterized in that: The mass ratio of the zinc oxide to the mixed solution of ethanol and water is 1:80-100.

4. The electrolyte for zinc-manganese battery according to claim 1, characterized in that: The temperature range of the heating is 60-80°C.

5. The electrolyte for zinc-manganese battery according to claim 1, characterized in that: The concentration of the trimethoxy-[4-[2-(4-methyl-2-pyridyl)-4-pyridyl]butyl]silane ethanol solution is 4 to 5 wt %.

6. The electrolyte for zinc-manganese battery according to claim 1, characterized in that: The vacuum drying temperature is 50-60°C.

7. The electrolyte for zinc-manganese battery according to claim 1, characterized in that: The vacuum drying time is 8 to 10 hours.

8. A method for preparing an electrolyte for a zinc-manganese battery according to any one of claims 1 to 7, characterized in that: The steps include: Mix potassium hydroxide, modified zinc oxide and water, and stir evenly to obtain the product.

9. The method for preparing an electrolyte for a zinc-manganese battery according to claim 8, characterized in that: The concentration of potassium hydroxide is 25-40 wt%.

10. The method for preparing an electrolyte for a zinc-manganese battery according to claim 8, characterized in that: The concentration of the modified zinc oxide is 2-8 wt %.

Citation Information

Patent Citations

  • Natural extract composition for zinc-manganese battery electrolyte, application of natural extract composition, zinc-manganese battery electrolyte and zinc-manganese battery

    CN107275655A

  • Zinc-oxide-containing alkaline zinc-manganese battery and preparation method thereof

    CN108172854A

  • 2-octanone condensation compound 2,6-pyridine sym-diformylhydrazine and application thereof

    CN103467371A

  • Organic-inorganic hybrid composite corrosion inhibitor as well as preparation method and application thereof

    CN114635137A

  • ELECTROLYTE SOLUTION FOR Ni-Zn FLOW BATTERY AND Ni-Zn FLOW BATTERY COMPRISING THE SAME

    KR1020160150158A